Psychosine remodels model lipid membranes at neutral pH - Zulueta Díaz, Yenisleidy de Las Mercedes (2018)
β-Galactosylsphingosine or psychosine (PSY) is a single chain sphingolipid with a cationic group, which is degraded in the lysosome lumen by β-galactosylceramidase during sphingolipid biosynthesis. A deficiency of this enzyme activity results in Krabbe's disease and PSY accumulation. This favors its escape to extralysosomal spaces, with its pH changing from acidic to neutral. We studied the interaction of PSY with model lipid membranes in neutral conditions, using phospholipid vesicles and monolayers as classical model systems, as well as a complex lipid mixture that mimics the lipid composition of myelin. At pH 7.4, when PSY is mainly neutral, it showed high surface activity, self-organizing into large structures, probably lamellar in nature, with a CMC of 38 ± 3 μM. When integrated into phospholipid membranes, PSY showed preferential partition into disordered phases, shifting phase equilibrium. The presence of PSY reduces the compactness of the membrane, making it more easily compressible. It also induces lipid domain disruption in vesicles composed of the main myelin lipids. The surface electrostatics of lipid membranes was altered by PSY in a complex manner. A shift to positive zeta potential values evidenced its presence in the vesicles. Furthermore, the increase of surface potential and surface water structuring observed may be a consequence of its location at the interface of the positively charged layer. As Krabbe's disease is a demyelinating process, PSY alteration of the membrane phase state, lateral lipid distribution and surface electrostatics appears important to the understanding of myelin destabilization at the supramolecular level.